Discussion of Some Questions in the Gear Strength Design - Mo Haijun; Xu Zhongyang; Zhang Zhiming (Jixie chuandong)
The gear strength is one of most important part in mechanical design. Several crisis problem will be mainly discussed which often confused and misunderstood about the calculation of the gear strength including the failure mode of gear,bending fatigue strength design,contact fatigue strength design,etc. The development of gear strength design in history and the current situation of it are also referred. This can be referenced for gear and other mechanical design or teaching,beside,it can also help the designer or student to get a deeper comprehensive and a better improvement on gear design and its background.